Biology Laboratory: Facilities, Infrastructure and Utilization in Biology Learning - Ghina Risnawati Aliyah; Etika Dyah Puspitasari (Universitas Ahmad Dahlan, 2022)
Permendiknas No 24 of the 2007 rule are a requirement to support practicum activities. This study aims to determine the suitability of laboratory infrastructure, types of biology laboratory utilization, and the constraints that affect biology practicum activities. This research is a literature study using 30 articles. Search for articles using online databases with search keywords for articles